Pengaruh Related Party Transaction, Capital Intensity, dan Kepemilikan Mayoritas Terhadap Agresivitas Pajak - Helpinsyah, Muhamad; Afridayani, Afridayani (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This investigation aims to understand the effect of related party transactions, capital intensity, and majority ownership on tax aggressiveness. Secondary data and quantitative methods are the tools researchers use. The research data was sourced through the non-cyclical consumer sector food and beverage subsector listed on the IDX during 2019-2023. Annual Reports and annual financial statements are the materials utilized in this investigation. A purposive sampling strategy was used to acquire the samples, which is 24 samples from the observation of 95 companies engaged in the consumer non-cyclical sector of the food and beverage subsector. Data analysis is a group-applied analysis pattern and applies random effect regression models and correlation regression models. Data is processed using the E-views13 system. The study outcome proves that the variables (RPT) Related to Party Transaction, (CINT) Capital Intensity, and (Kep. May) Majority Ownership affect Tax Aggressiveness (ETR). Results of the research of tax aggressiveness variables have a favorable impact caused by the influence of the Related Party Transaction variable, the tax aggressiveness variable has a negative impact due to the influence of the Capital Intensity variable, and the Tax Aggressiveness variable has a negative impact due to the influence of the Majority Ownership variable.